Pengembangan Sistem Pakar Analis Kepribadian Metode MBTI Studi Kasus : MTs Amdadiyah Karangrejo Kabupaten Kediri - Tito Pangestu; Patmi Kasih (Universitas Nusantara PGRI Kediri, 2026)
Understanding one's own personality, friends, and students is a crucial aspect in creating a healthy and supportive social and educational environment. A lack of understanding of individual characteristics often triggers conflicts, misunderstandings, and even psychological disturbances among adolescents. This study aims to develop an expert system based on the Myers-Briggs Type Indicator (MBTI) method, designed to analyze the personality types of adolescents, specifically middle school/MTs students aged 14–16 years. This system combines the Forward Chaining method for logical reasoning and the Certainty Factor for measuring the level of confidence in decision-making, resulting in more accurate outcomes with clear psychometric standards validated by experts. The objective of this research is to provide a personality analysis tool for students to better understand themselves, as well as for teachers or educators to adopt appropriate approaches toward students. The main benefits of this system are to enhance the effectiveness of the learning process and interpersonal relationships at school, as well as to serve as a private and efficient consultation tool. The system can also support character development and mental health programs for adolescents, aligning with the mission of holistic and sustainable education.